2014
DOI: 10.2308/ajpt-50697
|View full text |Cite
|
Sign up to set email alerts
|

Office-Level Characteristics of the Big 4 and Audit Report Timeliness

Abstract: SUMMARY: Recent changes in the audit and financial reporting environment have resulted in longer audit report lags and have increased the importance of identifying factors associated with a timely audit. We examine timeliness implications of office-specific attributes of the audit firm. Specifically, we examine whether office-specific industry expertise, office size, and the importance of the client to the local office are associated with audit delay (i.e., the time between fiscal year-end and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 38 publications
6
68
0
1
Order By: Relevance
“…This is because company with large size should have a high complexity and have a great asset, a good reputation public accounting firm will work professionally and faster to maintain client trust and will maintain its reputation. The research findings indicated that auditors would work professionally based on public accounting standard (Pourali, Jozi, Rostami, Taherpour, & Niazi, 2013;Whitworth & Lambert, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…This is because company with large size should have a high complexity and have a great asset, a good reputation public accounting firm will work professionally and faster to maintain client trust and will maintain its reputation. The research findings indicated that auditors would work professionally based on public accounting standard (Pourali, Jozi, Rostami, Taherpour, & Niazi, 2013;Whitworth & Lambert, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…We include a number of control variables in our analysis based on prior research (Ashton et al 1989;Ettredge et al 2006;Whitworth and Lambert 2014). These variables are defined in Table 1 and summarized below.…”
Section: Audit Delaymentioning
confidence: 99%
“…In addition, the authors found that client adoption of International Financial Reporting Standards (IFRS) did not appear to increase the ARL for industry specialist auditors as it did for other auditors. Whitworth and Lambert (2014) examined industry expertise at the office level, as well as office-specific characteristics. Similar to Habib and Bhuiyan (2011), they also found companies audited by industry expert auditors tend to have shorter ARL.…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%